A novel approach to generate attractors with a high number of scrolls. (February 2020) - Echenausía-Monroy, J.L.; Huerta-Cuellar, G.
Abstract: In this paper, a novel method for increasing the number of scrolls in a hybrid nonlinear switching system is presented. Using the definition of the "Round to the Nearest Integer Function", as a generalization of a Piece-Wise Linear (PWL) function, which is capable of generating up to a thousand of scrolls. An equation that characterizes the grown in the number of scrolls is calculated, which fits to the behavior of the system measured by means of the coefficient of determination, denoted R 2 . The proposed equation is based on obtaining as many scrolls as desired, based on the control parameters of the linear operator of the system. The work here presented provides a new approach for the generation and control of a high number of scrolls in a hybrid system. The results are verified for all the scenarios that the equations covers.